Causes, effects and impact of shortages of skilled artisans on contractor productivity - Mbeki, Sisa (Cape Peninsula University of Technology, 2015)
A dissertation submitted to the Department of Construction Management and Quantity Surveying, Faculty of Engineering at the Cape Peninsula University of Technology in fulfilment of the requirements for the degree of Master of Technology Construction Management === This study investigated the causes and impact of the effects of shortages of skilled artisans on contractor productivity. The objectives of the study were as follows: (i) to identify causes of shortages of skills during the construction production phases; (ii) to define the effects of shortages of skills during the production phase of a project; (iii) to examine how to deal with shortages of skills when they happen; (iv) to determine ways in which the shortage of skills may be reduced; (v) to determine whether shortages of skills cause poor contractor performance. The study was inspired by many international and local studies demonstrating a lack of concern for the impact of shortages of skilled artisans on project performance, and their effects on project time. The research method adopted for study was a survey of construction sites and staff within the NMC group in the Cape Peninsula metropolitan area of the Western Cape Province. The study collected data from 65 participants from 10 different NMC sites. The participants in the survey included Project managers, site managers, quantity surveyors and artisans on sites. The findings of the study revealed that there is lack of formal training of artisans; performance of artisans is not highly regarded and there is lack of motivation, these factors contribute to the shortages of skilled artisans. It is also evident that shortage of skills causes’ poor contractor performance and leads to poor quality of work. The researchers also found that, setting out errors occur due to lack of coordination between the main contractor and subcontractors and the lack of skills on the part of the artisans. In addition, inexperience on the side of the leading hand and / or supervisor and trades foremen and their inability to interpret the drawings contributed to rework during construction phase. A reason also given for shortage of artisans is that young people are afraid to get their hands dirty. Young people would rather work with computers than for engineering and its associated professions. It is recommended that to increase the supply of artisans some measures will have to be implemented to encourage young people to become artisans.